Musical Mirroring of Social Predicaments in Aristotle “GLOC-9” Pollisco Song Compositions: A Stylistic Analysis - Godeloson, Kayeceline G.; Abainza, Mica Mae; Nasayao, Florian L.; Noga, April Rose B.; Cuebillas, Princes I.; Mirate, Teodoro Jan M.; Ocampo, Darrel M. (Program Studi Pendidikan Bahasa Inggris, 2024)
This study was a stylistic analysis aimed at delineating the different social predicaments embedded in the ten (10) song compositions of GLOC-9. Particularly, it sought to: (1) identify the linguistic levels used in cascading the message and style of the songs along with semantics, lexicogrammar, phonology, and acoustic phonetics; (2) determine the stylistic devices under figures of speech used in the songs; (3) define the thematic levels presented in the songs along with the thematic concept and thematic statement; (4) specify the values or morals conveyed in the songs; and (5) discuss the social predicaments embedded in the songs. To further strategize the data gathering, the researchers used the Hallidayan Systemic-Functional Linguistic Theory in order to extract the different linguistic levels in the songs. Thus, the researchers found out that the social predicaments embedded in the song compositions that depicted social realities were: (1) social injustice; (2) violence; (3) prostitution; (4) drug addiction; (5) corruption; (6) gender discrimination; (7) killing; (8) poverty; and (9) brain drain mentality. Ergo, the results being demarcated in this study may help cultivate social awareness and provide positive implications in terms of transcending the minds of every Filipino, which is a crucial determinant in society and more especially in that of the nation.